A Conceptual Framework for Sustainable Tourism during Pandemic COVID-19 - Habib Ullah; Jawad Iqbal; Shahzad Ali Gill (Journal of Management Practices, Humanities and Social Sciences, 2021)
The main purpose of this research paper is to give a conceptual framework for sustainable tourism during pandemic like COVID-19 and also build a theoretical understanding of the key concepts relevant to sustainable tourism, which include perceived riskmitigating measures, community satisfaction, community involvement, community attachment, smart tourists' destination selection process, the impact of fear of COVID-19 and role of netizens in sustaining tourism. A qualitative research design is adopted in this study after taking insights from literature about sustainable tourism during the COVID-19 pandemic and conducting interviews with local community members directly participating in tourism activities and tourists who continued their tourism activities during these days. Finally proposes antecedents for sustainable tourism during the COVID-19 pandemic. The key ϐindings of this study reveal that society plays the main role in sustaining tourism during a pandemic. This study also provides a conceptual model for measuring sustainable tourism during the COVID-19 pandemic or any other pandemics like this COVID-19. And also, this study provides a deep understanding of those variables involved in the proposed conceptual framework. This study contributes to theory by providing latent variables for sustainable tourism useful for when the tourism industry is facing crises due to pandemic COVID-19. It also provides a conceptual framework with those variables that remain underexplored in previous studies. This conceptual model and literature review from previous studies add to the body of knowledge by introducing latent variables, while the conceptual model proposes relationships between these factors.